EFEK PROTEKSI ROYAL JELLY TERHADAP GAMBARAN HISTOPATOLOGI TESTIS TIKUS YANG DIINDUKSI BERBAGAI FAKTOR BAHAYA: TINJAUAN SYSTEMATIC REVIEW - Sarah Veronika Sianipar (2022)
Background: Infertility increases in both men and women. Male infertility may occur due to illness, exposure to hazardous chemicals in the workplace, nutritional deficiencies, consumption of certain drugs, environmental factors, bad habits, socioeconomic causes or other unknown causes. Royal jelly (RJ) is an efficient antioxidant that has been used to treat reproductive problems and infertility in men. Methods: Systematic review with literature search using Google Scholar, PubMed, and Science Direct. This research was conducted using the PRISMA-P 2009 flow chart. The literature used discusses royal jelly, testes, testicular histopathology, induction of harmful substances or factors. Results: There are 25 research literatures which show that the administration of royal jelly can improve the histopathological picture of the rat testes previously induced by various risk factors. Conclusion: The royal jelly intervention showed real protection against harmful effects on the testes through its content, namely: major royal jelly protein, polyphenols, flavonoids, vitamin C, and vitamin E.